Factors Affecting the Increased Share of Employment in the Services Sector - Abu Bakar, Siti Nasuhaa (2004)
Malaysian services sector is one of the rigorously growing sectors in terms of output and resource use. This sector has contributed more than two-third of total gross domestic product and absorbed more than half of total labour force. This sector is also less affected by the various economic instability such as economic recession. Our study is carried out in order to understand and to find out what are the factors that help the sustenance of this sector through the various economic disturbances with high employment. This study utilise time series data over 31 years beginning from 1970-2000. The services sector that are included in this study are electricity, gas and water services subsector, commercial services subsector, transportation, storage and communication services subsector and public services subsector. Since the main focus of this study is : employment, therefore the major variables are the employment in agricultural, manufacturing and services sector. This study employs recent time series techniques such as cointegration analaysis and error correction mechanism which enable to test the existence of the relationships among the factors. The results of the study show that the services sector is still one of the most rapidly growing sectors in response to new emerging industries such as the information and communication technology (ICT) and tourism (i.e. ecotourism and agrotourism). Government intervention also plays an important role to promote the growth of the . services sector by providing various infrastructures for the commercial, transportation, storage and communication and public sectors (i.e. education, community services and health services). To conclude, the services sector in Malaysia is dependent on manufacturing, vice versa.